Environmental & architectural phenomenology. Vol. 13, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2002)
Vol. 13, No. 1, Winter 2002 (includes “items of interest,” “citations received,” book review of Christopher Alexander's The Phenomenon of Life, and essays by Loretta Staples & Chris Desser).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals